Protecting vulnerable consumers from aggressive commercial practices - Kaprou, Eleni (2018)
The Unfair Commercial Practices Directive has been one of the most significant developments in European Consumer Law. It introduced provisions on aggressive commercial practices for the first time on a European level and provides the key definition of consumer vulnerability in European Consumer Law. This thesis draws attention to the previously overlooked topics of aggressive commercial practices and vulnerable consumers. It shows that the UCPD fails to ensure a high level of protection from aggressive practices for vulnerable consumers. The main reason for that is that the system of the UCPD which focuses on information and the average consumer is not well suited for aggressive practices and vulnerable consumers, which require a broader consideration of factors. Furthermore, it is argued that the vulnerable consumer standard in the UCPD is too narrow to adequately protect vulnerable consumers. A conceptualisation of consumer vulnerability based on the understanding that vulnerability is universal and can be experienced by anyone is suggested. The aggressive practices provisions are analysed and it is argued that inequality of power is at their core. The aggressive practices provisions suffer from lack of clarity that makes their application difficult. A key problem is that the average consumer is unsuitable for aggressive practices. This can be addressed with the introduction of the concept of resilience to pressure. Finally, it is argued that the use of empirical evidence in interpreting the UCPD can be beneficial for the protection of vulnerable consumers.